Antimicrobial resistance of bacteria isolated from veterinary clinics in the city of Ibague, Colombia - Sánchez, María del Pilar; Gutiérrez, Norma Patricia; Padilla, Mónica Yamile; Suárez, Leidy Lorena (Universidad y Salud, 2015)
Objective: To isolate bacteria circulating in veterinary clinics in the city of Ibague for knowing its antimicrobial resistance profile and in some cases, its ability to transfer this resistance to susceptible bacteria. Materials and Methods: Samples of 10 clinics that underwent bacterial culture, biochemical identification, antimicrobial susceptibility testing and bacterial conjugation to transfer this resistance were taken. The methodological design was quasi-experimental and the analysis of the results was made using descriptive statistics. Results: In all areas of the 10 clinical multiresistant potentially pathogenic bacteria which belonged to 8 of 16 species isolated were found. The microorganisms that occurred more frequently in different clinical places were: Staphylococcus intermedius, Acinetobacter baumannii, Pantoea agglomerans, Klebsiella pneumoniae and Burkhordelia cepacia. The places where multiresistant microorganisms were most frequently isolated were the outpatients’ floor and the clinical examination table. The resistance occurred mainly to amoxicillin and chloramphenicol. The study shows the presence of potential pathogens causing nosocomial infections, which constitute a reservoir of resistance genes to antibiotics for non-resistant pathogenic bacteria.